Digital Leadership as a Bridge Between Digital Transformation and Innovation Performance of Generation Z in SMEs - Achmad Sholihin; Sarah Astiti; Santi Suciningtyas; Rita Andini; Adji Seputro; Rohmah Kurniawati (Universitas Tidar, 2025)
Examining how digital leadership may improve innovation performance among millennial workers, this study seeks to answer the question of how Local Enterprises may successfully adopt digital transformation. Our main goal is to find out how digital leadership can help innovation succeed alongside digital transformation. Indonesia is home to 185,672 businesses, the vast majority of which are Local Enterprises. A total of 216 SMEs were selected for the study by applying Slovin's algorithm, which included a 5% margin of error. A systematic questionnaire was issued through Google Forms in order to gather data. This study used SmartPLS to look at how innovation performance, digital leadership, and digital transformation are related. Digital leadership and innovation performance are both profoundly affected by digital transformation, according to the results. Furthermore, digital leadership mediates the connection between digital transformation and innovation performance in addition to directly improving innovation performance. Based on these findings, digital leadership is essential for Local Enterprises to foster innovation through digital transformation. The use of self-reported data and the study's crosssectional methodology are two of the study's shortcomings. A more thorough comprehension of these processes could be achieved by future research that incorporates mixed-methods techniques and longitudinal studies. The relationship among digital leadership, digital transformation, and innovation in Local Enterprises is explored in this study.